2017
DOI: 10.1210/jc.2016-2645
|View full text |Cite
|
Sign up to set email alerts
|

LINE1 CpG-DNA Hypomethylation in Granulosa Cells and Blood Leukocytes Is Associated With PCOS and Related Traits

Abstract: Our study revealed strong association of single hypomethylated CpG-site with PCOS. Identification and characterization of more such methyl-CpG signatures in repetitive elements in larger study populations would provide valuable epigenetic insights into PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
0
17
1
Order By: Relevance
“…These elements have a high prognostic value in disease prediction and serve as important surrogate indicators of altered global methylation in disease states. Our studies show no change in total genomic 5mC or L1 5'-UTR methylation levels in PBLs or CGCs of women with PCOS compared to healthy controls; though a single CpG site (CpG -4) out of 22 CpG sites that were analyzed was found to be consistently hypomethylated and strongly associated with PCOS susceptibility and its traits of systemic and ovarian androgen-excess (155). We also noted that CGCs exhibited a hypomethylated status relative to PBLs (global as well as CpG-site specific hypomethylation), perhaps to facilitate the expression of ovary-specific genes that are otherwise not functional in PBLs.…”
Section: Epigenetic Studies Conducted In Women With Pcoscontrasting
confidence: 56%
“…These elements have a high prognostic value in disease prediction and serve as important surrogate indicators of altered global methylation in disease states. Our studies show no change in total genomic 5mC or L1 5'-UTR methylation levels in PBLs or CGCs of women with PCOS compared to healthy controls; though a single CpG site (CpG -4) out of 22 CpG sites that were analyzed was found to be consistently hypomethylated and strongly associated with PCOS susceptibility and its traits of systemic and ovarian androgen-excess (155). We also noted that CGCs exhibited a hypomethylated status relative to PBLs (global as well as CpG-site specific hypomethylation), perhaps to facilitate the expression of ovary-specific genes that are otherwise not functional in PBLs.…”
Section: Epigenetic Studies Conducted In Women With Pcoscontrasting
confidence: 56%
“…These findings raised the question of whether changes in DNA methylation were specific to the genomic region and tissue in women with PCOS; however, technical limitations, such as small sample size, could not be eliminated to elucidate these results. Conversely, a decline in the DNA methylation levels of a CpG located at the 5′-untranslated region of long interspersed nucleotide element-1 (L-1) correlated with a global hypomethylated state of the genome in the peripheral blood of women with PCOS compared with controls, as L-1 is a well-known marker for global DNA methylation (Sagvekar et al 2017).…”
Section: Dna Methylation In the Peripheral And Cord Blood From Women mentioning
confidence: 99%
“…Most studies focusing on DNA methylation and PCOS have been conducted in granulosa cells, which play a fundamental role in steroidogenesis and ovarian folliculogenesis and whose dysfunction correlates with the pathogenesis of the disease (Pellatt et al 2007;Lan et al 2015). Some studies have reported differences in the global content of DNA methylation in granulosa cells of women with PCOS compared with controls (Pruksananonda et al 2016, Xu et al 2016, Sagvekar et al 2017, Pan et al 2018. In particular, a global hypomethylated state of the genome in granulosa cells of women with PCOS (evidenced by a decline in the DNA methylation levels of L-1) correlated with the hormonal alterations of the disease (Sagvekar et al 2017).…”
Section: Dna Methylation In the Ovarian Tissue And Granulosa Cells Frmentioning
confidence: 99%
See 1 more Smart Citation
“…Polycystic ovary syndrome (PCOS) is one of the most prevalent endocrine metabolic disorders affecting about 5-10% women of reproductive age [1,2]. It is generally characterized by hyperandrogenism, polycystic ovary and anovulation, but also associated with metabolic dysfunction, cardiovascular risk, abnormal granulosa cells (GCs) proliferation as well as arrest of follicle growth [3,4]. The clinical symptoms and signs of PCOS vanished or irregular menstruation, difficulty in pregnancy, acne, as well as thick, dark and smooth skin patches [5].…”
Section: Introductionmentioning
confidence: 99%